FRI0228 Ugt1a1 genetic variants are associated with increases in bilirubin levels in rheumatoid arthritis patients treated with sarilumab. (15th June 2017) - Damask, A; Boyapati, A; Hamilton, JD; Hamon, S; Paccard, C; Parrino, J; Adelsberg, J van; Graham, NM; Penn, J; Lopez, A; Reid, J; Overton, J; et al.
Abstract : Background: Sarilumab is a human mAb that blocks IL-6 from binding to both membrane-bound and soluble IL-6Rα. Variants in the UGT1A1 gene have been shown to be strongly associated with increased unconjugated bilirubin levels in patients treated with tocilizumab, another IL-6Rα inhibitor. 1, 2 UGT1A1 encodes the enzyme responsible for the glucuronidation of bilirubin and variation in this gene is also responsible for Gilbert's syndrome, a mild benign condition characterized by elevations in unconjugated bilirubin and jaundice. The underlying main genetic variation responsible for Gilbert's syndrome has been identified as a TA repeat located in the promoter of UGT1A1 (UGT1A1*28 allele), which is in linkage disequilibrium with a single nucleotide polymorphism, rs6742078, previously associated with higher bilirubin levels after tocilizumab treatment. 1 Objectives: To test for an association between rs6742078 and bilirubin levels in RA patients treated with sarilumab. Methods: DNA was collected from patients enrolled in MOBILITY (NCT01061736 ), which evaluated the efficacy and safety of sarilumab + methotrexate (MTX) in RA patients with inadequate response to MTX. The pharmacogenetic analysis was conducted in 599 Caucasian patients treated with MTX + sarilumab (150 or 200 mg q2w) or placebo. Log-transformed unconjugated and total bilirubin levels were analyzed at baseline and over the treatment period (using maximum bilirubin). Results: There was a strong association between the rs6742078 TT genotype and higher unconjugated bilirubin levels. The least squares mean (SE) for patients at baseline with the TT genotype was 0.48 (0.02) mg/dL vs 0.25 (0.009) and 0.21 (0.009) mg/dL for those with GT and GG genotypes, respectively ( p =1.02×10 -21 ). After sarilumab treatment, the difference between genotype groups increased over the course of the study ( p =4.3×10 -10 ; Figure). In the binary analysis of maximum total bilirubin in sarilumab-treated patients, the TT genotype was significantly associated with mild bilirubin elevations (OR =34.7; p =1.2×10 -8 ; Table). Conclusions: The association observed between the rs6742078 TT genotype in UGT1A1 and unconjugated bilirubin elevations in sarilumab-treated patients is consistent with previous observations in tocilizumab-treated patients. These findings suggest that sarilumab-related increases in bilirubin levels are likely benign and caused by common genetic variation in UGT1A1 and are not due to underlying liver injury. References: Mori et al. Mod Rheumatol. 2012;22:515–523. Lee et al. Pharmacogenet Genomics. 2011;21:365–374. Acknowledgements: This study was sponsored by Sanofi Genzyme and Regeneron Pharmaceuticals, Inc. Editorial support was provided by MedThink SciCom and funded by Sanofi Genzyme and Regeneron Pharmaceuticals, Inc. Disclosure of Interest: A. Damask Shareholder of: Regeneron Pharmaceuticals, Inc, Employee of: Regeneron Pharmaceuticals, Inc, A. Boyapati Shareholder of: Regeneron Pharmaceuticals, Inc, Employee of: Regeneron Pharmaceuticals, Inc, J. Hamilton Shareholder of: Regeneron Pharmaceuticals, Inc, Employee of: Regeneron Pharmaceuticals, Inc, S. Hamon Shareholder of: Regeneron Pharmaceuticals, Inc, Employee of: Regeneron Pharmaceuticals, Inc, C. Paccard Shareholder of: Sanofi R&D, Employee of: Sanofi R&D, J. Parrino Shareholder of: Regeneron Pharmaceuticals, Inc, Employee of: Regeneron Pharmaceuticals, Inc, J. van Adelsberg Shareholder of: Regeneron Pharmaceuticals, Inc, Employee of: Regeneron Pharmaceuticals, Inc, N. Graham Shareholder of: Regeneron Pharmaceuticals, Inc, Employee of: Regeneron Pharmaceuticals, Inc, J. Penn Shareholder of: Regeneron Pharmaceuticals, Inc, Employee of: Regeneron Pharmaceuticals, Inc, A. Lopez Shareholder of: Regeneron Pharmaceuticals, Inc, Employee of: Regeneron Pharmaceuticals, Inc, J. Reid Shareholder of: Regeneron Pharmaceuticals, Inc, Employee of: Regeneron Pharmaceuticals, Inc, J. Overton Shareholder of: Regeneron Pharmaceuticals, Inc, Employee of: Regeneron Pharmaceuticals, Inc, A. Baras Shareholder of: Regeneron Pharmaceuticals, Inc, Employee of: Regeneron Pharmaceuticals, Inc, A. Shuldiner Shareholder of: Regeneron Pharmaceuticals, Inc, Employee of: Regeneron Pharmaceuticals, Inc, C. Paulding Shareholder of: Regeneron Pharmaceuticals, Inc, Employee of: Regeneron Pharmaceuticals, Inc